Long Term Risks of Proton Pump Inhibitor Administration: A Literature Review - Andi Kristanto; Randy Adiwinata; Josephin Rasidi; Beatrice Belinda Phang; Sheila Adiwinata; Timoteus Richard; Willy Brodus Uwan; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Proton pump inhibitor (PPI) has become drug of choice for acid related disease. However, PPI tend to be overprescribed and becoming one of the highest burden for health cost. Some studies showed that PPI are prescribed unnecessarily. Recent evidences showed raised concerns over long term effects of PPI consumption. Several long term side effects such as increased incidence of gastric polyps, micronutrient absorption disorders, infections, and osteoporosis have been yearly discussed. In recent years there has been increased attention to new side effects such as dementia, chronic renal failure, and cardiovascular disorders. Therefore, some health associations had issued warning and guidance regarding long term PPI prescription.